Promoting sustainable development and its business potential: a case study on Cement Industries (Sabah) Sdn Bhd employees / Nurul Fatin Effendi - Effendi, Nurul Fatin (2010)
The research is conducted at the Cement Industries (Sabah) Sdn Bhd which is to know on their employees understanding on the sustainable development in the company, and collecting the information on its safety and health, environment and energy efficiency. With this information, the researcher may know it is easy for the company to promote the sustainable development towards the company. And by implementing the sustainable development, it has a business potential for the company, which can enhance their business and also can preserve the environment. There is also some recommendation that stated in this research, which could improve and enhance the company's sustainable development.